Psoriasis rupioides with marked nail abnormalities in a HIV-positive patient - Chlebicka, Iwona; Reich, Adam; Szepietowski, Jacek (Dermatology Review/Przegląd Dermatologiczny, 2016)
Introduction. Psoriasis rupioides is a rare type of psoriasis. Although a description of it is easy to find in most textbooks of psoriasis, it does not have a place in the ICD-10 classification, and there have been very few case reports published in the literature on this characteristic psoriasis subtype. Objective . To present a case of this rare type of psoriasis. Case report. We present the case of a young man with psoriasis rupioides, which was diagnosed on the basis of anamnesis and clinical features. The patient also demonstrated marked nail abnormalities. Because of the patient’s history and abnormalities of blood smear, virological tests were performed, which confirmed the suspected presence of HIV infection. Conclusions . Presented case indicates the necessity of diagnostic procedures for HIV infection in patient with less or atypical types of psoriasis.